PENYULUHAN PENINGKATAN KUALITAS MUTU TANAMAN KOPI ROBUSTA PADA KUPS PAYUANG SIRUKAM KECAMATAN PAYUNG SEKAKI KABUPATEN SOLOK - Rika Hariance; Rini Hakimi; Nuraini Budi Astuti; Rian Hidayat; Yulinda Yulinda (LPPM Universitas Andalas, 2023)
The Social Economics Department of the Faculty of Agriculture initiated an academic partnership with KKI Warsi in implementing MBKM learning, research and community service. The purpose of this collaboration is in an effort to improve the quality of learning at the University and as a bridge for the transfer of knowledge from the university to the whole community as a form of the tri dharma of higher education. This community service activity was carried out at the KUPS Payung Sirukam social forestry group located in Nagari Sirukam, Payung Sekaki District, Solok Regency which was fostered by KKI Warsi. This service was carried out because the Robusta coffee plant in Nagari Sirukam is a plant that is still a legacy from the Dutch colonial period, where the cultivation process was not carried out intensively by farmers. This cultivation problem affects the quality of coffee. Thus, it is necessary to conduct counseling on Robusta coffee cultivation to farmers who are members of KUPS Payung Sirukam. From this counseling, farmers gain knowledge about good quality coffee beans, the maintenance process through good coffee cultivation patterns, and how to vegetatively rejuvenate coffee seedlings. Rejuvenation of coffee plants is one of the efforts that can be made in order to produce coffee plants that are the same as the main plants to maintain the quality of the sirukam coffee and shorten the harvesting life of the plants.